THE INFLUENCE OF SOCIAL NETWORKS ON PEER SATISFACTION AS MEDIATED BY RESOURCE ACCUMULATION - Uuganbold.T,; Erkhembayar.L, (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
This article examines the infuence of social networks on peer satisfaction by mediating social support among Mongolian top manufacturer employees. Our primary goal is to investigate the two pathways through which instrumental and multiplicity networks relates to peer satisfaction. I use the theory of social capital as the conceptual grounding for the general predictions in this study because it provides an explanation for why workplace relationships influence peer satisfaction. Research drawing from social capital theory predominantly focuses on the resources that are gained from network relationships. A Socio-metric and traditional questionnaire is used to collect data from 120 employees at the Company. Data is analyzed using UCINET VI and SPSS software. The finding indicates that out-degree centrality of instrumental network is positively associated with peer satisfaction as mediated by informational support. And in-degree centrality of multiple network is positively relationship with peer satisfaction as mediated by emotional support. In addition, we identified how employee’s cognitive attitude of co-worker’s team behavior affect the network structure. The practical and theoretical implications of the study findings are discussed.